The Social Status Analysis of Freedom Writer Movie’s Character Based Upon the Uttered Language Variation - Nur Muhammad Ardiansyah (International Consortium of Education and Culture Research Studies, 2021)
Due to the expanding demand of exploration in linguistic studies, this research was specifically made in answering one of the fundamental question related with the discourse of societal status in domain of literary work. Upn such goal, this research aims to unveil the link between social class and the way a person speak through their variation of the language spoken in daily basis. Since this research addresses the use of language variation in literaty work, the required data were taken specifically from a movie entitled as Freedom Writers. The analysis utilizes textual analysis as the mean of interpretation and data processing, due to the fact this research is carried in qualitative manner. By following the theoretical framework of language variation from William Labov, researcher is finally able in unveiling the finding of this study. Concisely, it is showed that in most cases, language variation is heavily influenced by speaker.